KEY DETERMINANTS OF 21ST CENTURY TEACHER EFFECTIVENESS DOMAINS USING NOMINAL GROUP TECHNIQUE - Wan Nurfarahiyah W. Liah; Hutkemri Zulnaidi; Husaina Banu Kenayathulla, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
In the evolving landscape of 21st century education, the key determinants of teacher effectiveness have expanded to not only pedagogical skills but encompasses technological competencies, social-emotional intelligence and the integration of cultural elements in teaching. Using the Nominal Group Technique (NGT), a structured, systematic method, this study aims to determine and rank the key determinants of 21st century teacher effectiveness derived from the expert’s consensus. A total of seven experts in this field from various educational backgrounds were involved in this study. Grounded by the experts’ consensus and prominent authors' notion, the findings demonstrated four essential key determinants: pedagogical skills and instructional strategies, professional development and reflective teaching, social-emotional and interpersonal skills, and inclusivity and cultural responsiveness of teacher effectiveness in modern classroom teaching. As this study employed NGT to derive the key findings, it provides valuable insight and valid reference for future researchers, educational institution, school teachers, and policymakers to explore these suggested domains in teacher effectiveness and applied the proposed model to their teaching practices.